Crusaders of New France : A Chronicle of the Fleur-de-Lis in the Wilderness Chronicles of America, Volume 4 - Munro, William Bennett, 1875-1957; Johnson, Allen, 1870-1931 (Salt Lake City, UT : Project Gutenberg, 2004)
"Crusaders of New France" by William Bennett Munro is a historical account published in the late 1910s. This work delves into the French colonial efforts in North America during the 17th century, chronicling the ambitions and challenges faced by France in establishing New France. Munro explores the socio-political context of France under the Bourbon monarchy and highlights key figures in French exploration and colonization, emphasizing both their successes and failures in this endeavor. The opening of the book sets the stage by outlining the significant factors that positioned France to lead in overseas expansion during the age of exploration. It describes France's military might, governmental centralization, and the influential role of the Catholic Church, asserting that these elements made France a formidable candidate for establishing a New World empire. The narrative introduces historical figures such as Louis XIV and highlights the early expeditions led by Jacques Cartier, whose quests illustrate the complex interplay of ambition and practicality in the French colonial ambition. In this segment, Munro establishes a perspective on how French aspirations for territory and wealth ultimately collided with the realities of a new and challenging environment. (This is an automatically generated summary.)
Release date is 2004-06-01
Produced by the Online Distributed Proofreading Team, from images provided by the Million Book Project
Keywords: Canada -- History -- To 1763 (New France); New France -- Discovery and exploration